2010
DOI: 10.1016/j.ijrobp.2010.07.353
|View full text |Cite
|
Sign up to set email alerts
|

Normal Tissue Complication Probability Analysis of Acute Gastrointestinal Toxicity in Cervical Cancer Patients Undergoing Intensity Modulated Radiation Therapy and Concurrent Cisplatin

Abstract: Purpose/Objective(s): There have been over 19 randomized trials and three meta-analyses addressing the issue of concomitant chemoradiotherapy (CRT) in carcinoma cervix. The benefit was largely limited to early stage and in post-operative settings (FIGO IIIB accounting for \30%). In developing countries, advanced disease at presentation, poor nutrition including anemia, low tolerability and poor compliance, inadequate supportive therapy and financial constraints pose a major challenge for CRT practice. To evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 0 publications
1
18
2
Order By: Relevance
“…Multiple previous retrospective and prospective studies have found that the use of IMRT is associated with reduced normal tissue dose and toxicity compared with conventional radiation techniques (ie, either anteroposterior/posteroanterior or 4-field box methods) (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(26)(27)(28)(29). However, IMRT has not been widely tested in multicenter trials of cervical cancer, in particular, for the large international population of patients undergoing definitive CRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple previous retrospective and prospective studies have found that the use of IMRT is associated with reduced normal tissue dose and toxicity compared with conventional radiation techniques (ie, either anteroposterior/posteroanterior or 4-field box methods) (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(26)(27)(28)(29). However, IMRT has not been widely tested in multicenter trials of cervical cancer, in particular, for the large international population of patients undergoing definitive CRT.…”
Section: Discussionmentioning
confidence: 99%
“…The IMRT plans consisted of 7 to 9 coplanar fields or 2 to 3 coplanar arcs and were designed to optimize bowel and pelvic bone marrow sparing and maintain PTV coverage. The key organ dosimetric constraints were the bowel volume receiving !45 Gy (V 45 ) <200 cm 3 and pelvic bone marrow V 10 and V 20 <90% and <75%, respectively, according to validated normal tissue complication probability models (16,18). The "bowel" was contoured beginning from the axial slice situated 1 cm superior to the superior-most slice containing the PTV and continuing to its most inferior extent in the pelvis, with the outermost extent of the small and large bowel loops outlined on each axial CT slice, as described previously (16).…”
Section: Therapeutic Intervention and Quality Assurancementioning
confidence: 99%
See 1 more Smart Citation
“…The small intestine is an organ that could develop acute gastrointestinal (GI) toxicity after radiation. Roeske et al 25 and Simpson et al 26 reported that the increasing bowel V45 was correlated with increased GI toxicity in patients with cervical cancer who are undergoing IMRT. Another investigation clearly showed that Grade 2 or more severe acute bowel toxicity was highly correlated with the intestinal cavity receiving 40-50 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…26 Similarly, Simpson et al proved such a dependency for the volume of intestine receiving the dose above 45Gy and the intensification of post radiation reaction. 27 Erpolat et al proved, however, that post-radiation reaction in G ≥ 2 degree in 3D technique compared with IMRT technique related to anemia was present respectively in 2% and 27% of the patients, as for leukopenia respectively in 41.5% and 53%, as for neutropenia respectively in 12% and 24.5% of the patients and as for thrombocytopenia respectively in 0 and 4.5%. The values of V10, 20, 30, 40 were better in IMRT technique, but they did not relate to the diminished post-radiation reactions.…”
Section: Discussion Of Resultsmentioning
confidence: 95%